Triggering of protection mechanism against Phoneutria nigriventer spider venom in the brain. - Catarina Rapôso (Public Library of Science (PLoS), 2014)
Severe accidents caused by the "armed" spider Phoneutria nigriventer cause neurotoxic manifestations in victims. In experiments with rats, P. nigriventer venom (PNV) temporarily disrupts the properties of the BBB by affecting both the transcellular and the paracellular route. However, it is unclear how cells and/or proteins participate in the transient opening of the BBB. The present study demonstrates that PNV is a substrate for the multidrug resistance protein-1 (MRP1) in cultured astrocyte and endothelial cells (HUVEC) and increases mrp1 and cx43 and down-regulates glut1 mRNA transcripts in cultured astrocytes. The inhibition of nNOS by 7-nitroindazole suggests that NO derived from nNOS mediates some of these effects by either accentuating or opposing the effects of PNV. In vivo, MRP1, GLUT1 and Cx43 protein expression is increased differentially in the hippocampus and cerebellum, indicating region-related modulation of effects. PNV contains a plethora of Ca(2+), K(+) and Na(+) channel-acting neurotoxins that interfere with glutamate handling. It is suggested that the findings of the present study are the result of a complex interaction of signaling pathways, one of which is the NO, which regulates BBB-associated proteins in response to PNV interference on ions physiology. The present study provides additional insight into PNV-induced BBB dysfunction and shows that a protective mechanism is activated against the venom. The data shows that PNV has qualities for potential use in drug permeability studies across the BBB.